From legacy media to going viral : generational media use and citizen engagement - Wicks, Robert H.; Morimoto, Shauna A.; Wicks, Jan LeBlanc (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"From Legacy Media to Going Viral: Generational Media Use and Citizen Engagement examines how the prominent media available shapes each rising generation of citizens. The authors discuss how global and national events along with the media each generational group most frequently accessed defined these groups. Drawing on interdisciplinary social science insights into social media and civic and political engagement, the book contextualizes the civic and political rise of the Millennials and Gen Z with comparative insights from Gen X and the Baby Boomers. With a focus on emergent patterns of American citizenship, the authors examine issues such as a decline in social trust, new and sustained patterns of civic and political engagement, and the continuing importance of political consumerism. Looking beyond the impact of media on youth and issues of civic and political generational change, this book explores how the media accessible to each American generation contributes to that generation's collective experience thus solidifying their civic and political attitudes. The book will be of interest to students and scholars concerned with civic and political engagement, political consumerism and media use, in the areas of media studies, advertising, communication, journalism, political science and sociology"--
Keywords: Mass media -- Political aspects -- United States; Generations -- Political activity -- United States; Intergenerational relations -- United States; Communication in politics -- United States; Social media and society -- United States; POLITICAL SCIENCE / Civics & Citizenship